Tinjauan Fikih Muamalah Mengenai Wanita dalam Transaksi Ekonomi Syariah - Yahya Riva’i; Hasbi Abdul Al-Wahhab KH; Muhammad Rasyid Ridlo; Muhajirin (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study discusses the concept of ahliyah (legal competence) which is quite an important discussion to be parsed, studied and discussed. Bearing in mind that legal competence has an important position in a contract because it is a condition that must be fulfilled by the subject of the contract which has implications for whether the contract can be considered valid or not; Legal competence in question turns out to be ahliyatul ada' (active skills) in fiqh muamalah. In this study, researchers examined the concept of ahliyah in the perspective of Islamic law (the opinion of the scholars) contained in fiqh books. The purpose of this research is to provide an understanding of the community as legal subjects, so that the contracts they enter into are correct according to Islamic law. This research is a normative juridical research that uses a type of Syara'-Fiqh approach (statue approach), case approach (case approach) and conceptual approach (concept approach). In carrying out legal actions, a person must first be declared competent to act according to the law. So in this study the researcher describes it in a descriptive-qualitative form. The results of study show that woman are increasingly dominating in economic transactions, especially in e-commerce media.